The expression -22x + 3y = 6 in the form ax + by + c = 0 is -2x + 3y - 6 = 0
<h3>Linear Equations</h3>
The given equation is:
-2x + 3y = 6
Comparing the equation above with ax + by + c = 0
Rewrite -2x + 3y = 6 in the form ax + by + c = 0
-2x + 3y - 6 = 0
If -2x + 3y - 6 = 0 is compared with ax + by + c = 0
a = -2, b = 3, c = -6
Therefore, the expression-22x + 3y = 6 in the form ax + by + c = 0 is -2x + 3y - 6 = 0
Learn more on linear equations here: brainly.com/question/14323743
If we observe the graph it crosses x-axis at the following points:
1) x = - 2
2) x = - 5
This means, x+ 2 and x + 5 are the factors of the polynomial. A polynomial can be expressed as the product of its factors. So we can express the given polynomial as (x + 2)(x + 5)
Thus the answer to above question is option C
7/5y. you add the 2/5y to the 5/5y and get 7/5y
19 ÷ 25= 0.76
0.76 ⇒ 76%
She got a C on the test.
Hoped this helped.
~Bob Ross®
The answer would be 25 because the square root of 25 is 5.